The vacancy ordering produces a new cubic monocarbide: ReC. (December 2018) - Liang, Y.; Yang, J.; Xi, L.; Liu, C.; Zhang, G.; Zhang, W.
Abstract: The search of novel compounds with special structures and unusual functionalities continues to be a central challenge to modern materials science. Although transition metal carbides usually can form a wide range of vacancies, the precise and robust ordering of the vacancies seldom occurs in the field of crystal structures. Here, we report a new cubic ReC that is isomorphic with NbO. It can be derived from the NaCl structure by systematically removing one-fourth of metal and non-metal atoms. The vacancy ordering not only restores the stability of ReC but also triggers an unexpectedly high hardness. We further find that the NaCl class of carbides exhibits the maximal stability for a valence electron number of 8 electrons per formula unit, and less or more electrons lead to the decrease of stability. The structural modification from the NaCl type to the NbO type is a result of the reluctance of extra electrons to fill the dd non-bonding and pd antibonding bands. Our findings resolve the longstanding structural puzzle of ReC and provide a new principle for the structural stability of other carbides, nitrides, and oxides. Graphical abstract: Highlights: A new cubic ReC, isomorphic with NbO, is derived from the NaCl structure by removing one-fourth of metal and nonmetal atoms. The NaCl class of TMCs has the maximal stability for the valence electron number of 8 electrons per formula unit. The crossover from the NaCl type to the NbO type stems from the reluctance of extra electrons to fill the unfavorable bands. The newly identified ReC exhibits an unexpectedly high hardness.